Violencia against children and adolescents - Augusto, María de los Milagros (2021)
Violence against children and adolescents are multiple and complex problems, made  visible as a necessity to be faced by the states, in particular from the International Convention on the Rights of the Child. The internal order of Argentina continues to advance with specific legislation of national and local order. The Argentine Civil and Commercial Code - hereinafter CCCN - in force since 2015, reinvigorates the responsibility to effect the adequate development of minors, fundamentally in relation to the express recognition of progressive capacity, the process of dejudicialization of the issues referred childhood, adolescence and family, which can be resolved in the administrative sphere, and the prohibition of mistreatment (art. 647 of the CCCN). This article proposes some cases with resolutions through multidisciplinary approaches, with the implementation of useful tools to give answers to these realities; in whose eradication we are constantly, increasingly and creatively committed.